2013
DOI: 10.1371/journal.pone.0079953
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Comparison of Cowpox Viruses Reveals a New Clade Related to Variola Virus

Abstract: Zoonotic infections caused by several orthopoxviruses (OPV) like monkeypox virus or vaccinia virus have a significant impact on human health. In Europe, the number of diagnosed infections with cowpox viruses (CPXV) is increasing in animals as well as in humans. CPXV used to be enzootic in cattle; however, such infections were not being diagnosed over the last decades. Instead, individual cases of cowpox are being found in cats or exotic zoo animals that transmit the infection to humans. Both animals and humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 18 publications
6
86
0
Order By: Relevance
“…This virus used to be enzootic in cattle; however, such infections have not been diagnosed over the last decades, while individual cases of cowpox have been repeatedly found in cats or exotic zoo animals that were responsible for human transmission. 8,13,16,17,24,26 It is not possible to conclude that CPXV was the causal agent of the lesions reported in the domestic ruminants in our study; in fact, its low genomic load can be the result of interference caused by multiple viral agents replicating at the same time in the same target cell. On the other hand, the presence of CPXV DNA in the pathological samples of the domestic ruminants lead us to speculate that the virus may use these animal species as reservoirs to spread and persist in the environment through the scab material produced by other epitheliotropic viruses.…”
mentioning
confidence: 61%
“…This virus used to be enzootic in cattle; however, such infections have not been diagnosed over the last decades, while individual cases of cowpox have been repeatedly found in cats or exotic zoo animals that were responsible for human transmission. 8,13,16,17,24,26 It is not possible to conclude that CPXV was the causal agent of the lesions reported in the domestic ruminants in our study; in fact, its low genomic load can be the result of interference caused by multiple viral agents replicating at the same time in the same target cell. On the other hand, the presence of CPXV DNA in the pathological samples of the domestic ruminants lead us to speculate that the virus may use these animal species as reservoirs to spread and persist in the environment through the scab material produced by other epitheliotropic viruses.…”
mentioning
confidence: 61%
“…6A) and make up a C-type lectin-like domain, which is suggested to be a ligand for the NK cell inhibitory receptor NKR-P1 (17). Recently, genome sequences of a number of CPXV strains from clinical isolates have been determined (38). By comparing CPXV012 homologs of these strains and of other published CPXV and orthopoxvirus strains, we identified two major clusters (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…A comparison of 41 genes conserved among all known poxviruses revealed that CPXV strains group into three distinct clades (38). Members of these clades are more closely related to variola virus, camelpox virus, and taterapox virus (clade 1), CPXV (clade 2), or vaccinia virus (clade 3) (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations